A Review on Cluster Head Selection Algorithms for Wireless Sensor Networks - Tamilselvi, S; Rizwana, S (International Journal of Computer Sciences and Engineering, 2019)
Energy-efficient cluster head selection algorithms are significant in Wireless Sensor Networks (WSN) to improve the lifetime of the networks. Various cluster head selection algorithms were designed in WSN to enhance the network lifetime. The tiny sensor nodes are grouped to form a cluster and clustering is an important technique in WSN. The selection of cluster heads greatly affects the throughput of the network. Still, it is a challenging task. Different approaches and algorithms have been proposed for the efficient CH selection in WSNs. In this paper, a brief survey is made about the various CH selection algorithms in the recent scenario. The advantages and disadvantages of the most important algorithms are highlighted.